Pedagogiceskomu fakul'tety SPBGUFKe im. P. F. Lesgafta - 95 let - Kostjucenko, V. F. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
Becoming of the Russian sports education and orientation in a professional training the author traces on the basis of the retrospective analysis of work of pedagogical faculty Saint Petersburg state P.F. Lesshaft's university of physical culture.